New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas - Bocek, Matej (Zootaxa, 2017)
The recently collected material of Diatrichalus Kleine, 1926 from New Guinea and the Moluccas was studied. Four new species are described: D. buruensis sp. n., D. manokwarensis sp. n., D. mindikensis sp. n., and D. robustus sp. n. The diagnostic morphological characters are described in detail and illustrated. New records of previously described species are reported from several localities in New Guinea and D. mancus (Kleine, 1926) is for the first time reported from the Australian continent. Some Diatrichalus have similar male genitalia and are considered as closely related. Despite supposed relationships, they differ in the presence of secondary elytral longitudinal costae, which have been traditionally used for the delimitation of genera in net-winged beetles.
Keywords: brouci; Animals; New Guinea; mužské pohlaví; Male; Coleoptera, Net-winged beetles, Metriorrhynchina, Diatrichalus, Australasia, new species, morphology, taxonomy; Austrálie; zvířata; Australia; Nová Guinea; Coleoptera